Increasing sunflower production in Uganda through seed importation and developing local sunflower hybrids: Increasing sunflower production in Uganda through seed importation and developing local sunflower hybrids - WALTER O ANYANGA; ROLAND JAMES OCAN; BRIAN OMARA; GRACE AJIBU (Journal of Oilseeds Research, 2023)
There is great potential for growing sunflower in Uganda. For the last decade, the farmers of Uganda have picked interest in the growing of sunflower. This is because of availability of ready market from the oil millers. However, production is constrained by limited available high yielding sunflower hybrids. Much of the seed is imported from International Seed Companies. Single cross hybrids and three-way cross hybrids were evaluated to check which types gives better yield, oil content and other desirable traits. Preliminary results showed that a number of three-way cross hybrids yielded better than the imported hybrids. We are therefore contemplating towards emphasis on scaling out three-way cross compared to single cross hybrids which is generally grown worldwide.